Texts by Petrus Wilhelmi de Grudencz in the context of the late medieval ars poetriae - Bartosz Awianowicz (Muzyka)
Since the discovery of Petrus Wilhelmi de Grudencz (1392–after 1452) by Jaromír Černy, Grudencz's life and work have become a subject of many studies, but until recently his strictly poetic oeuvre still awaited research. The aim of the present article is to interpret Petrus' texts in the context of medieval artes poetriae, handbooks combining elements of grammar, poetics and above all rhetorics, with which the composer could have become familiar as early as in his native Prussia, and was certainly exposed to them during his long studies in Kraków (1418–30). The handbooks used the most at the Kraków University at the time were Poetria nova by Geoffrey of Vinsauf and Laborintus by Eberhard of Bremen. In the then capital of Poland, or some time later in Vienna, Petrus could have come across De arte prosayca, metrica et rithmica by Jean de Garlande.